Walking as Precarious Public Pedagogy - Powell , Kimberly (Journal of Public Pedagogies, 2019)
This paper is located in extensive walking and narrative community-based research in the historic and ethnic neighborhood of San Jose Japantown, California, in the United States (U.S.). I consider public pedagogy through precarity, drawing from scholars who theorize the term through an ethics and politics of vulnerability, indiscernibility and relationality. In my consideration of walking as precarious public pedagogy, I work with a concept of movement as the gatherings of varying temporalities across histories, activities, humans, and nonhuman agents to underscore the entanglement of US social and economic infrastructures, discriminatory practices of spatialized place politics, and local narratives situated in place politics. I also consider the paradoxical relationship of constraints and possibilities inherent in precarity, arguing that a consideration of walking as precarious public pedagogy is indeterminant, a becoming that is entangled within a vulnerable existence.